2007
DOI: 10.18011/bioeng2007v1n3p237-244
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Behavior of Ndvi Measured With an Active Optical Sensor for Different Varieties of Sugarcane

Abstract: Active optical sensors are a new approach for site specific nitrogen management on real time and they have been successfully used on grain crops. This work consisted in evaluating the behavior of the Normalized Difference Vegetation Index (NDVI) using a commercial active optical sensor on 28 sugarcane varieties, as well as analyzing the temporal behavior of this index for each variety throughout the initial 150 days of their productive cycle. The NDVI data was collected with 90, 120 and 150 days after planting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…This result contrasts with the necessity of specific calibrations, as suggested by Frasson et al (2007), as a function of the morphological differences among the different varieties and their consequences in spectral behavior. Therefore, the factors that seem to influence canopy sensor readings the most are crop vigor and canopy volume, usually dependent on edaphic and climate conditions, rather than on factors associated with the cultivated variety, such as leaf color or plant architecture.…”
Section: Methodscontrasting
confidence: 71%
See 1 more Smart Citation
“…This result contrasts with the necessity of specific calibrations, as suggested by Frasson et al (2007), as a function of the morphological differences among the different varieties and their consequences in spectral behavior. Therefore, the factors that seem to influence canopy sensor readings the most are crop vigor and canopy volume, usually dependent on edaphic and climate conditions, rather than on factors associated with the cultivated variety, such as leaf color or plant architecture.…”
Section: Methodscontrasting
confidence: 71%
“…However, the lowest fitting in the first and second experiments could be a reflection of the presence of varieties with different production potentials that could have responded in different ways to climate, soil, and management conditions throughout the crop cycle, resulting in different crop vigor and canopy volume in the same field. According to Frasson et al (2007), the abovementioned statement on specific calibration sounds reasonable.…”
Section: Methodsmentioning
confidence: 99%
“…And that is what makes the sensors to be promising while evaluating nitrogen stress. Many studies were realized to estimate nitrogen deficiency in corn [3], wheat [20], edible beans [21], cotton [22], citrus [23], barley [24] and sugarcane [25]. These authors showed great potential to use sensors to estimate nitrogen content in crops.…”
Section: Aspects Of Use In the Field And What Can Affect The Measuremmentioning
confidence: 99%